2021
DOI: 10.1002/slct.202003920
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Sensors for Water Detection in Organic Solvents and their Applications

Abstract: Moisture or trace water detection at a very low level in organic solvents and other chemical reagents has great significance in the chemical and industrial process. At present, reports on chemical sensors for moisture are still in the early development phase and need continuous improvements. Recently, several approaches have been proposed for the easier detection of water content in the organic solvents. In this review article, we have summarized recent reports on chemical sensors used to detect water in organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 88 publications
1
28
0
Order By: Relevance
“…Extremely high sensitivity for low concentrations of water was also demonstrated ( Table 1 ), with the lowest detection limit for water of 0.018% (v/v) calculated in DMSO. This detection limit is in line with the limits of the most sensitive sensors for water in organic solvents reported to date ( Huang et al, 2021 ), and indicates that the sensor reported herein represents a highly sensitive detection method ( Kumar et al, 2021 ). Of note, all aqueous studies were conducted in double deionized water, so that no interference and/or fluorescence quenching occurred due to residual metal ions.…”
Section: Resultssupporting
confidence: 88%
“…Extremely high sensitivity for low concentrations of water was also demonstrated ( Table 1 ), with the lowest detection limit for water of 0.018% (v/v) calculated in DMSO. This detection limit is in line with the limits of the most sensitive sensors for water in organic solvents reported to date ( Huang et al, 2021 ), and indicates that the sensor reported herein represents a highly sensitive detection method ( Kumar et al, 2021 ). Of note, all aqueous studies were conducted in double deionized water, so that no interference and/or fluorescence quenching occurred due to residual metal ions.…”
Section: Resultssupporting
confidence: 88%
“…As far as organic solvents are concerned, trace water is treated as one of the most pervasive impurities, which is difficult to solve in laboratory settings and in the chemical industry. 1,2 Therefore, it is quite necessary to develop simple, reliable, and fast sensors for water detection in organic solvents. Traditionally, Karl Fischer titration and gas chromatography are broadly used for the detection of water content.…”
Section: Introductionmentioning
confidence: 99%
“…The detection and quantification of small amounts of water are of great significance in several fields of chemistry and industry. 1 For example, in chemistry, particularly in organometallic chemistry, the presence of water will lead to the quenching of the reactive organometallic compounds, inhibiting the reaction or lowering the yields, and furthermore due to the high reactivity of the aforementioned organometallic reagents, the presence of water can, under some circumstances, lead to catastrophic failures, such as fires and explosions. In addition, an industrial process where the presence of water plays a crucial yet detrimental role is petroleum based fuels.…”
Section: Introductionmentioning
confidence: 99%